Hookah smoking behavior initiation in the context of Millennials. (August 2016) - Castañeda, G.; Barnett, T.E.; Soule, E.K.; Young, M.E.
Abstract: Objectives: This study aims to examine current hookah users' perceptions, attitudes, and normative beliefs regarding hookah smoking to further elucidate the rise in hookah smoking prevalence among young adults (aged 18–24 years) and reveal why hookah smoking is perceived as less harmful than other forms of tobacco consumption. Study design: Qualitative. Methods: Data from six focus group interviews with hookah smokers aged between 18 and 24 years were analyzed using a grounded theory approach. Focus groups were evenly split between frequent and infrequent hookah users, and were predominantly composed of college students, with two groups of hookah users consisting of 18–24 year olds of non-student status. Results: Hookah users shared a much larger set of positive hookah smoking behavioral beliefs as opposed to negative behavioral beliefs. Generational traits served as the overarching commonality among the behavior performance initiation determinants observed. The most notable generational trends observed were within the cultural category, which included the following millennial characteristics: autonomy, personalization, novelty appeal, convenience, globally oriented, entertainment, collaboration, health conscious, and valuing their social network. Conclusions: Millennial hookah users revealed mindfulness regarding both potential negative and positive reasons stemming from continued hookah use; however, behavioral beliefs were primarily fixated on the perception that hookah smoking was a healthier alternative to cigarette smoking. Future implications for this study's findings include generating more positive ways to express these traits for young adults; policy implications include raising hookah bar age limits, implementing indoor smoking restrictions, and limiting the ease of accessibility for purchasing hookah supplies. Highlights: We observed young adult hookah users' perceptions, attitudes, and normative beliefs regarding hookah smoking. Generational traits served as the overarching commonality among the hookah smoking initiation determinants observed. Several generational trends identified included autonomy, personalization, novelty appeal, and globally oriented. Health policy implications include raising hookah bar age limits and implementing restrictions on indoor smoking.